Colchicine and high-intensity rosuvastatin in the treatment of non-critically ill patients hospitalised with COVID-19: a randomised clinical trial. Issue 2 (24th February 2023) - Shah, Tayyab; McCarthy, Marianne; Nasir, Irem; Archer, Herb; Ragheb, Elio; Kluger, Jonathan; Kashyap, Nitu; Paredes, Carlos; Patel, Prashant; Lu, Jing; Kandel, Prakash; Song, Christopher; et al.
Abstract : Objective: To evaluate the effect of colchicine and high-intensity rosuvastatin in addition to standard of care on the progression of COVID-19 disease in hospitalised patients. Design: A pragmatic, open-label, multicentre, randomised controlled trial conducted from October 2020 to September 2021. Follow-up was conducted at 30 and 60 days. The electronic medical record was used at all stages of the trial including screening, enrolment, randomisation, event ascertainment and follow-up. Setting: Four centres in the Yale New Haven Health System. Participants: Non-critically ill hospitalised patients with COVID-19. Interventions: Patients were randomised 1:1 to either colchicine plus high-intensity rosuvastatin in addition to standard of care versus standard of care alone. Assigned treatment was continued for the duration of index hospitalisation or 30 days, whichever was shorter. Primary and secondary outcome measures: The prespecified primary endpoint was progression to severe COVID-19 disease (new high-flow or non-invasive ventilation, mechanical ventilation, need for vasopressors, renal replacement therapy or extracorporeal membrane oxygenation, or death) or arterial/venous thromboembolic events (ischaemic stroke, myocardial infarction, deep venous thrombosis or pulmonary embolism) evaluated at 30 days. Results: Among the 250 patients randomised in this trial (125 to each arm), the median age was 61 years, 44% were women, 15% were Black and 26% were Hispanic/Latino. As part of the standard of care, patients received remdesivir (87%), dexamethasone (92%), tocilizumab (18%), baricitinib (2%), prophylactic/therapeutic anticoagulation (98%) and aspirin (91%). The trial was terminated early by the data and safety monitoring board for futility. No patients were lost to follow-up due to electronic medical record follow-up. There was no significant difference in the primary endpoint at 30 days between the active arm and standard of care arm (15.2% vs 8.8%, respectively, p=0.17). Conclusions: In this small, open-label, randomised trial of non-critically ill hospitalised patients with COVID-19, the combination of colchicine and rosuvastatin in addition to standard of care did not appear to reduce the risk of progression of COVID-19 disease or thromboembolic events, although the trial was underpowered due to a lower-than-expected event rate. The trial leveraged the power of electronic medical records for efficiency and improved follow-up and demonstrates the utility of incorporating electronic medical records into future trials. Trial registration: NCT04472611 .